2014
DOI: 10.1111/1759-7714.12073
|View full text |Cite
|
Sign up to set email alerts
|

Polymorphisms in DNA repair genes of XRCC1, XPA, XPC, XPD and associations with lung cancer risk in Chinese people

Abstract: Background: The carcinogenic chemicals and reactive oxygen species in tobacco can result in DNA damage. DNA repair genes play an important role in maintaining genome integrity. Genetic polymorphisms of DNA repair genes and smoking may contribute to susceptibility of lung cancer. Methods: In this hospital-based case-control study, we investigated the relationship between 13 tagging single nucleotide polymorphisms (SNPs) in base excision repair pathway and nucleotide excision repair pathway genes, smoking, and l… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
13
0
1

Year Published

2016
2016
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 19 publications
(15 citation statements)
references
References 48 publications
1
13
0
1
Order By: Relevance
“…Although reports on the SNP in the XPA gene have been published previously, these did not share a relation with the significant XPA SNPs that was identified in our current study. Most of those previous studies mainly focused on identifying the relationships between the SNPs and cancer risk in different populations 17,38,4049. Only Gao et al50 found a prognostic importance related to the XPA rs10817938 C allele, which indicated that it is a potential functional SNP and a biomarker for prognosis in oral squamous cell carcinoma patients, similarly with our results, no significant association of rs2808668 polymorphism with OSCC prognosis observed.…”
Section: Discussionsupporting
confidence: 85%
“…Although reports on the SNP in the XPA gene have been published previously, these did not share a relation with the significant XPA SNPs that was identified in our current study. Most of those previous studies mainly focused on identifying the relationships between the SNPs and cancer risk in different populations 17,38,4049. Only Gao et al50 found a prognostic importance related to the XPA rs10817938 C allele, which indicated that it is a potential functional SNP and a biomarker for prognosis in oral squamous cell carcinoma patients, similarly with our results, no significant association of rs2808668 polymorphism with OSCC prognosis observed.…”
Section: Discussionsupporting
confidence: 85%
“…It remains controversial on the association of rs2808668 with different type of cancers risk. In lung cancer and breast cancer, previous studies reported that rs2808668 polymorphism was significantly associated with cancer susceptibility[ 17 , 20 ]. However, no significant association between rs2808668 polymorphism with pancreatic cancer, larynx cancer could be observed[ 33 , 34 ].…”
Section: Discussionmentioning
confidence: 99%
“…rs2808668 is also a T to C substitution located -514bp from the transcriptional start site. Previous studies have found the positive association between rs2808668 polymorphism and lung cancer, breast cancer risk[ 17 , 20 ]. However, no report has been provided to show the association of these two polymorphisms with OSCC.…”
Section: Introductionmentioning
confidence: 99%
“…Owing to the important role of XPA protein in NER pathway, the association between XPA polymorphisms and cancer risk remains a hot spot of research. By now, several epidemiological studies have been performed to determine of the association with the risk of cancer, including colorectal cancer 36 , laryngeal cancer 37 , lung cancer 38 , and B-cell lymphoma 39 .…”
Section: Introductionmentioning
confidence: 99%